Oi! Get Off Our Train - John Burningham (A Red Fox Book SIngapore, 1989)
A tale of a little boy speeding through the night on his dream-train to far off lands where endangered animals beg for a lift. The author also wrote Mr Gumpy's Outing, Would You Rather and Come Away From the Water. Granpa won the 1984 Emil/Kurt Maschler Award.
Keywords: Climates -- Climates; Conservation -- Conservation; Sustainability -- Sustainability